Cell Design and Routing of Jobs in a Multisite Make-to-Order Enterprise - Gupta, Manoj; Bose, R. P. Jagadeesh; Dutta, Partha (Proceedings of the International Conference on Automated Planning and Scheduling, 2016)
Make-to-order is a production process where the businesses build the product only after an order from the customer is received. A large enterprise may have many such make-to-order shops distributed geographically. The cost and time for executing a job in each of these shops may vary. Therefore, it is important for a multisite enterprise to judiciously decide on where to process the jobs. Ideally, an enterprise would like to minimize the cost (or maximize the profit) while meeting the deadlines and at the same time maximize the utilization of the shops. The time to execute jobs can vary based on how the shops are laid out (the design of shops) and the decision of how jobs are routed (among the various shops). Predicting (or estimating) the likely turnaround time (and cost) for various jobs across the different shops enables the routing decision process. In this paper, we address the two important problems of (i) cell-design and (ii) turnaround time prediction and routing of jobs across various shops. We propose (i) a novel approach based on graph partitioning and set cover heuristic to generate a set of cell designs for a shop, (ii) a framework based on machine learning techniques to predict the turnaround time of jobs across various shops, and (iii) a routing algorithm based on dynamic programming and local search heuristic to route jobs such that the overall profit is maximized. We present results of applying the proposed approaches on real-life datasets from a multisite print shop enterprise.